Tinjauan Marketing Online @taqychansaffron Pada Sosial Media Instagram Dalam Perspektif Syariah - Rahila Amanatul Ummah; Qurrota'ayun Zakiyati; Sarah Sobrina Balqis; Wakhidah Nur Rohmatul Laili (ITB AAS INDONESIA Surakarta, 2022)
The research approach used is a narrative qualitative approach. Research that aims to understand the phenomenon of what is experienced by research subjects holisticallya and by way of description. The focus of the discussion in this study is sharia online marketing used by PT Berkah Abadi Empat Bersaudara, this business model, all transactions online must be facilitated by website the relevant PT Berkah Abadi Empat Bersaudara is enganged in herbal medicine, namely saffron, cashmere, honey, etc, packaged in the Taqychansafron’s brand and has been certified by BPOM, GMO, ISO food and Halal MUI. Taqychansafron’s marketing strategy uses social media Instagram which relies on and adheres to the marketing of the Prophet transparency and no element of farud. Instagram sosial media users are now about 300 milion users, this number exceeds the number of people in Indonesia, but it is facing competition , a strong viral marketing effect and accessible on mobile devices.